2015
DOI: 10.1039/c5ra16068e
|View full text |Cite
|
Sign up to set email alerts
|

Acid catalysed cross-linking of poly vinyl alcohol (PVA) by glutaraldehyde: effect of crosslink density on the characteristics of PVA membranes used in single chambered microbial fuel cells

Abstract: In the present study, acid catalysed cross-linking of poly vinyl alcohol (PVA) with varying concentrations of glutaraldehyde was analyzed and the cross-linked PVAs were utilized as membrane separators in single chambered microbial fuel cells (MFCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(114 citation statements)
references
References 43 publications
(46 reference statements)
1
113
0
Order By: Relevance
“…[34] The peak at 1,733 cm −1 is related to stretching vibrations of C=O groups, which come from the residual vinyl acetate repeat units in the PVA [26] and the residual acetyl groups in the CS. [31] For the crosslinked PVA/CS samples, the peaks at 1,598 cm −1 corresponded to NH 2 was almost eliminated, which can be ascribed to the amino group in CS was consumed due to GA crosslinking. The absorption peak at 1,598 cm −1 was related to the amide type II of CS as well as the NH 2 blending vibration.…”
Section: Results and Discussion 31 | Atr-ftir Of Crosslinked Pva/cmentioning
confidence: 93%
See 3 more Smart Citations
“…[34] The peak at 1,733 cm −1 is related to stretching vibrations of C=O groups, which come from the residual vinyl acetate repeat units in the PVA [26] and the residual acetyl groups in the CS. [31] For the crosslinked PVA/CS samples, the peaks at 1,598 cm −1 corresponded to NH 2 was almost eliminated, which can be ascribed to the amino group in CS was consumed due to GA crosslinking. The absorption peak at 1,598 cm −1 was related to the amide type II of CS as well as the NH 2 blending vibration.…”
Section: Results and Discussion 31 | Atr-ftir Of Crosslinked Pva/cmentioning
confidence: 93%
“…[31] The process of crosslinking was performed by putting nanofibers into 20 ml crosslinking agent solution with varying concentrations of GA (0.1%, 0.3% and 0.5%) and keeping 30 min for crosslinking at room temperature. In this study, the isopropyl was used as the main crosslinking solvent because it will not lead to destroy of the morphology as a non-solvent of the PVA/CS composite nanofibers, which is different from the method of previous study.…”
Section: Preparation Of Crosslinked Pva/cs Composite Nanofibersmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeolites are well known as porous materials, and several have proton conducting properties [8,9]. PVA is well known as a water-soluble polymer, and many studies on zeolite-PVA composite films have been reported for various applications [10][11][12][13][14][15], and most of these studies utilized an aldehyde cross-linking reaction in acidic condition (Figure 2) [15,16]. Cross-linking of PVA can be carried out in thin film form, which is very important in this study, since the PVA can easily be cross-linked by penetration of the cross-linker aqueous solution after composite film preparation.…”
Section: Introductionmentioning
confidence: 99%